Location Authentication Methods for Wireless Network Access Control - Lichun Bao (2008 IEEE International Performance, Computing and Communications Conference, 2008)
Location-based service provisioning is of great interests to wireless Internet service providers. However, the essential mechanism, location authentication, can easily become the target of network hackers for free-riding and attacks. We identify two aspects for improvements at the network providers to enforce location authentication for network access control location-based key distribution and run-time location verification, and propose solutions to enforce network access control based on location, which we refer to as LENA (Location-Enforced Network Access). First, we designed a location authentication and authorization protocol based on Diffie-Hellman algorithm, which securely authenticates the location claims of mobile wireless devices, and distributes shared keys for data encryption purpose. Secondly, we employ a mobility management protocol to guarantee that the mobile devices are physically at where they claim to be when they access the network. These two steps can separately enforce location based network access control, or be combined. LENA climinates the dependence on expensive hardware devices in order to localize the mobile devices, and solves a couple of possible attacks to the system. The computations, communication, and the memory requirement are evaluated and validated using simulations.